Histological assessment of variations in sexual maturity of cod (Gadus morhua L.) at the Flemish Cap (north-west Atlantic) - Saborido-Rey, Fran; Junquera, Susana (ICES Journal of Marine Science, 1998)
7 páginas, 4 figuras, 4 tablas. A histological method is used to detect the proportion of both adult and recruit females at the beginning of gonad development, in summer, a few months after spawning. At this time it is difficult to make a visual diagnosis of the sexual maturity stage. The proportion of females with postovulatory follicles is used to determine the length and age at maturity in the year of sampling, and the proportion of females in the cortical alveoli and/or vitellogenic stages is used to estimate the same parameter for the following year. Variations in age and length at maturity during the period 1992–1995 were analysed by comparing the respective maturity curves of both the "previous spawners" and the "next-year spawners" females. A drastic decrease in both the age and the length at maturity is observed in this period and it seems likely that the age at maturity of female cod became fixed at around age 3 at the end of the period analysed. The possibility that this could be a density-dependent response of the stock at the Flemish Cap is discussed. This research was undertaken with funding from European Union (Research Project AIR1 CT92-0558). Peer reviewed